(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2023)
The effect of addition of ultra-fine material i.e. Alccofine on the properties of coal bottom ash assisted concrete has been studied in this study. Alccofine is added in steps in the 40% bottom ash concrete to revive the properties of bottom ash concrete. A proportion of 5 to 20% has been added as an alternative to cement. Results showed that replacement of cement with Alccofine has improved the compressive strength of the concrete.